PERTUMBUHAN DAN FAKTOR KONDISI T. NAVALIS PADA SALINITAS BERBEDA DI HABITAT ALAMI - Yumima Sinyo; Tamrin Robo (UNIVERSITAS KHAIRUN, 2022)
T. navalis has high reproducibility and is widely distributed according to physiological tolerance and conditional factors. The purpose of this study was to analyze the growth and condition factors of Teredo navalis Linnaeus 1758 in the mangrove root habitat of Avicennia sp. This type of research is a case study, using the purposive sampling method. Data collection was carried out at two research stations, starting with determining the roots and stems of Avicennia sp mangroves in 70 cm pieces, then observing growth and taking samples. The results showed that the growth of T. navalis in the root habitat of Avicennia sp at treatment S1 (7‰) was 9.96±0.06 gr and the highest at treatment S3 (21‰) was 18.20±0.02 gr. salinity and absolute weight growth of T. navalis with a quadratic pattern with the equation Y = 0.1524x+11.345 R2 = 0.1506, and the optimum point of salinity of 14‰ media can produce maximum absolute weight growth of T.navalis (Y) = 15.33 gr. The results of the calculation of the value of the condition factor (FK) on the relationship between length and weight of T. navalis in the root habitat of Avicennia sp W = 26.29 + 0.39x. Based on the graph of the relationship between length and weight, the value of Y = 00338x2 + 1.8421 + 57,115 and R2 = 0.5834.